Vegetative methods and dune renegotiation as efforts to restore functions and minimize natural disasters - Nurul Laili Fadhilah; Bayu Dwi Anggono; Pratiwi Puspitho Andini; Rosita Indrayati (University of Merdeka Malang, 2024)
The dune plays a crucial role in the community life of Sumberkejayan Village, Mayang Subdistrict, Jember Regency. The decline in its functionality began in 2017, coinciding with a tornado and a reduction in the water discharge from community water sources around the dune. In response to these developments, the team initiated a program aimed at restoring the functionality of the dune within the Sumberkejayan Village area. The objective of this program is twofold: to reinstate the functionality of the dune and to emphasize the importance of caution in the buying and selling of dunes by its owners. Vegetative and renegotiation methods are employed through replanting (reforestation) using Sengon Solomon planting media. Sengon Solomon was selected for its rapid development compared to other types of sengon. Concurrently, renegotiation serves as a remedy in the buying and selling process, addressing disparities in agreements regarding dunes. Renegotiation provides alternative solutions for disadvantaged parties, aiming to restore the terms of the agreement and the conditions of the involved parties.